PENERAPAN PASAL 70 UNDANG-UNDANG NOMOR 30 TAHUN 1999, DALAM PERKARA INVESTMENT AGREEMENT, ANTARA HARY TANOESOEDIBJO MELAWAN SITI HARDIYANTI RUKMANA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 97 B/PDT.SUS-ARBT/2016) - Nuraisyah Indri Widya; Stanislaus Atalim (Jurnal Hukum Adigama, 2021)
Arbitration is a way of resolving a civil dispute outside the general court based on an arbitration agreement made in writing by the parties. In article 70 of law number 30 of 1999 concerning arbitration and alternative dispute resolution, there are provisions regarding the cancellation of an arbitration verdict. There are many interpretations regarding the terms of the cancellation of the arbitration verdict, this makes the arbitration law ineffective in resolving disputes such as in the case of seizure of shares in PT. Cipta Televisi Pendidikan Indonesia. In this case, the Central Jakarta District Court canceled the arbitration verdict on reasons that are beyond Article 70. In addition, after an appeal was made to the Supreme Court, in its decision the Supreme Court stated that the arbitration verdict could not be implemented and canceled the decision of the Central Jakarta District Court which canceled the arbitration verdict, this creates legal uncertainty for the parties because there is no clarity and resolution of the problem for the problem in dispute.